Formative Evaluation of School Work Plan (RKS) Implementation in Curriculum Management: Evidence from a Vocational High School in Indonesia - Kardina, Tri; Aprianti, Ria; Suhaimi,; Sulistiyana, (Jurnal Paedagogy, 2026)
This study aims to conduct a formative evaluation of the implementation of curriculum programs outlined in the School Work Plan (RKS) at SMKN 1 Martapura using the Context, Input, Process, and Product (CIPP) evaluation model. The study employed an evaluation research design with a qualitative approach. The primary informant was the Vice Principal for Curriculum Affairs, while additional data were obtained from the Principal and selected teachers for source triangulation. Data were collected through in-depth interviews, document analysis, and limited observations. The data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing/verification, guided by the CIPP evaluation framework. The results showed that curriculum program planning was developed based on the analysis of the Education Report and the School Medium-Term Development Plan (RKJM), reflecting a data-driven planning approach. From the input perspective, teacher readiness and the availability of practical learning facilities remained important factors influencing curriculum implementation. From the process perspective, most curriculum programs included in the School Work Plan had been implemented, including teacher professional development activities, curriculum synchronization with industry needs, and teaching factory-based learning, although their implementation had not yet achieved optimal effectiveness. From the product perspective, improvements were observed in several educational indicators, including literacy, numeracy, and the alignment between school programs and industry demands. However, the quality of classroom learning still requires improvement, particularly in the implementation of innovative instructional strategies. Unlike previous CIPP-based studies that primarily focused on standalone educational programs, this study evaluates curriculum management embedded within the School Work Plan as an integrated strategic planning instrument in vocational education. These findings suggest that the effectiveness of curriculum program implementation within the School Work Plan is influenced by data-driven planning, human resource readiness, the availability of learning facilities, and the transformation of teachers’ pedagogical practices.